The Geriatric Forensic Psychiatry Rotation at University of Chicago: Utilization and Educational Benefit of a Subspecialty Rotation in Psychiatric Residency Training - Shima, Carolyn; Finkel, Sanford; Spitz, Deborah; Goldstein, Amanda I. (Frontiers in Psychology, 2019)
Ten years ago, the University of Chicago Medical School Department of Psychiatry and Behavioral Neuroscience established a geriatric forensic psychiatry rotation for fourth-year residents as one option in a required experience in forensic psychiatry. The rotation’s emphasis was to learn about cases of testamentary capacity and undue influence. The program was supervised by a senior faculty member, an experienced clinician, board-certified in Geriatric Psychiatry. RESULTS Over the past decade, three of the 11 residents have pursued careers in forensic psychiatry, while another has become a geriatric psychiatrist. More than half of the respondents have pursued geriatric and/or forensic work following their graduations, and all believe that what they learned in the rotation applied to their general practice work. All 11 indicated that the rotation increased their interest in and understanding of forensic work. Ten “strongly agreed” that the geriatric forensic psychiatry rotation was a valuable learning experience. On average, trainees worked on 4.64 forensic cases over the course of the rotation and attended 2–3 trials or depositions. Over the last three years of the program, all three of the participating residents have chosen to complete a forensic fellowship following the rotation. CONCLUSION Residents affirm that a geriatric forensic psychiatry rotation is a valuable learning experience, one that has utility after their graduation. The University of Chicago Department of Psychiatry and Behavioral Neuroscience is committed to continuing this rotation as an important part of their forensic experience in resident education and to encourage more interest in the area of geriatric psychiatry.